Enhancing English Speaking Skills through PowerPoint Presentation Techniques: A Study of EFL Learners - Salainti, Engelina; Wijayanti, Lisma Meilia (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The researcher did a study to investigate the impact of presentation techniques in elevating English-speaking skills among English as a Foreign Language (EFL) learners. This study applied a quantitative approach and employed a structured questionnaire using Likert-Scale items to assess students' perceptions of how the presentation methods impact their speaking abilities. A sample of university EFL learners especially the students in General English class of Elementary and Pre-Intermediate I participated in the study, providing insights into their experiences with presentation-based learning activities. Descriptive and inferential statistical analyses were conducted to evaluate the relationship between using presentation techniques and the perceived improvement in speaking proficiency. The findings reveal that students perceive presentation techniques as significantly beneficial for enhancing their speaking skills and fostering greater engagement and confidence during oral communication tasks. This research highlights the importance of integrating effective presentation methods in EFL instruction to promote learners’ speaking development. It provides recommendations for educators seeking to enhance language acquisition in the classroom.